If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = y + 19 Reorder the terms: 25 = 19 + y Solving 25 = 19 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 25 + -1y = 19 + y + -1y Combine like terms: y + -1y = 0 25 + -1y = 19 + 0 25 + -1y = 19 Add '-25' to each side of the equation. 25 + -25 + -1y = 19 + -25 Combine like terms: 25 + -25 = 0 0 + -1y = 19 + -25 -1y = 19 + -25 Combine like terms: 19 + -25 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6
| 18-(9-5x)x=4 | | 3(y+4)=33 | | 678=789 | | 4-2b=-8(4b+7) | | -2(x-5)+3=25 | | 13/8=p-5/2 | | -5x^2-3=77 | | 15x-5=14x | | 12-2x=w | | 14=23+s | | 7(x-4)=-26+7x | | -5x^2+3=-77 | | 6x-54=5x-55 | | 14=23+5 | | 5-x=11-2x | | 4x+20+5x-5=87 | | f(X)=9830(x)+50(x) | | 5y^2-10x=2 | | 7(6-2a)=5(-3a+1)x | | -5(1-3p)=35+7p | | 3x+-2y=3 | | 2x+3x=5.70 | | 2x-5=8x+10-x | | 0=4x^2+32x+48 | | f+3/8=21/4 | | 4a+.4=1.6 | | f(x)=4x^2+32x+48 | | 6x^2+xy-2y^2+7x+7y-3=0 | | y=-5x+90 | | 0=.25x^2+x-15 | | 6x-2y+24=0 | | 5x^2+25x+4=2 |